THE STRENGTH AND POWER OF KABADDI AND ATHLETICS PLAYERS - Pramanick, Subrata; Chowdhuri, Prasoon; Dutta, Rajib; Rahaman, Aminur (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this study was to compare shoulder strength and leg power between Kabaddi and Athletics players. The male subjects for the study were chosen by the present researchers. The participants in the study were those who competed in inter-college district tournaments. The participants were between the ages of 18-25 years. Twenty players from each of the games Athletics (n=20) and Kabaddi (n=20) were chosen by the researchers. A simple random sampling method was used to select the 40 subjects. The researchers used the Standing Broad Jump to collect data on leg power, which was measured in meters. Pull-ups were used to test shoulder strength, and the total number of pull-ups was counted. The statistical package SPSS was used to compare shoulder strength and leg power of Kabaddi and Athletics players and used the mean, standard deviation, and independent t-test. The level of significance was set at 0.05 to test the hypothesis. The findings show that the strength of the shoulders did not differ significantly between Kabaddi and Athletics players. Also, no significant difference was found in leg power between Kabaddi and Athletics players.